EFFECT OF CHLORAL HYDRATE ON METABOLIC RATE OF LABEO ROHITA (HAM) AND POECILIA RETICULATA (PETERS) - SHARMA, L. L.; SHARMA, S. K. (Journal of Indian Fisheries Association, 2015)
Comparative impact of chloral hydrate anaesthesia on the metabolic rate of Indian major carp Labeo rohita and larvivorous fish Poecilia reticulata was assessed. Observation on the oxygen consumption rate (OCR) revealed that in common guppies OCR was substantially low (1.105 and 1.097 mg/g!hr) at 0.1 and 0.25 gil concentrations of chloral hydrate as against OCR of 1.487 mg/g/hr in the control. Fry of L.rohita in groupÂ· showed lower metabolic rates in the control as well as treated conditions as compared to the individuals of this fish. This may be due to sympathetic psychophysiological reflex of grouped fish. Higher dose of chlo1Â·al hydrate (0.25g!l) also caused higher OCR probably due to distress. Application of chloral hydrate also favoured lesser release of metabolic wastes (ammonia and carbon dioxide). There was significant positive correlation between time and oxygen consumption, whereas, for time and OCR this relationship was negative. Regression of chloral hydrate doses for OCR and time has also been calculated.